(±)-Stagonosporopsin A, stagonosporopsin B and stagonosporopsin C, antibacterial metabolites produced by endophytic fungus Stagonosporopsis oculihominis. (October 2021) - Wang, Ju-Tao; Li, Hui-Yuan; Rao, Rao; Yue, Jing-Yi; Wang, Guo-Kai; Yu, Yang
Graphical abstract: Highlights: Two undescribed secondary metabolites were isolated from endophytic fungus Stagonosporopsis oculihominis . (±)-Stagonosporopsin A is a pair of enantiomer. Stagonosporopsin C exhibited moderate inhibitory activity against Staphylococcus aureus subsp. aureus ATCC29213. Abstract: A successive investigation of the endophytic fungus Stagonosporopsis oculihominis isolated from Dendrobium huoshanense led to the discovery of two undescribed secondary metabolites, (±)-stagonosporopsin A and stagonosporopsin B, and a new natural product, stagonosporopsin C. (±)-stagonosporopsin A is a pair of enantiomer. The structures of the isolated compounds, including their absolute configurations, were elucidated based on extensive spectroscopic analyses, electronic circular dichroism (ECD) calculations and X -ray diffraction. Stagonosporopsin C exhibited moderate inhibitory activity against Staphylococcus aureus subsp. aureus ATCC29213 with an MIC50 value of 41.3 μ M.